Analysis of Bullying Behavior of Broken Home Children in High School - Bintari, Zhoya (Medan State University, 2024)
The purpose of this research is to find out how the form of bullying behavior and what are the motives of bullying behavior of broken home children in SMAN. In this study, researchers used qualitative research methods. Respondents in this study amounted to 7 people. Using purposive sampling technique with the criteria of broken home families, being sensitive, broken homes experienced from the age of (6-17 years), have committed acts of bullying. Data collection techniques used through observation, interviews and documentation. Data analysis techniques are carried out by using an Interactive model of quantitative analysis from Milles and Huebeman which consists of data reduction, data presentation and conclusions. The results of the discussion show that the bullying behavior of broken home children in SMAN is still classified as a lot where the actions taken in the form of verbal bullying such as labeling names, ridicule, insulting, alienating, belittling and saying harsh words. While non-verbally such as pinching, pushing, pinching the head, pulling the shirt, pulling the headscarf and hitting. The motive for these actions is influenced by family disharmony, pressure in the family, ridicule obtained by school friends which triggers children to commit these acts of bullying.